Detoxification of Organophosphorus Compounds (OPs) by Bacillus megaterium in Agricultural Water Waste - Alasadi, Fatima Karim Khudair; Abbas, Zainab M. (Central Asian Journal of Medical and Natural Science, 2025)
Organophosphorus compounds (OPs) are a large family of synthetic pesticides commonly used in modern agriculture because of their insecticidal activity. Unfortunately, their repeated and often non-selective use has caused considerable environmental pollution (i.e., in soils and waterways) and massive impacts on non-target organisms (including people). OPs are neurotoxic compounds whose toxicology is primarily a result of the inhibition of acetylcholinesterase, and their environmental persistence through agricultural runoff may lead to long-term ecotoxicological effects. Therefore, there is an urgent need for effective, sustainable, and environmentally friendly methods for removing these compounds from polluted environments. The objective of this study was to examine the potential of Bacillus megaterium, a robust and metabolically diverse Gram-positive bacterium, to detoxify organophosphorus compounds in simulated agricultural wastewater under controlled laboratory conditions. The bacterium was isolated using HiCrome Bacillus Agar, a selective and differential medium that promotes the growth of Bacillus species and identifies these species based on pigmentation of their colonies. Biochemical tests (gram staining, catalase, urease, methyl red, and indole tests) confirmed that the isolate was Bacillus megaterium. There were bioremediation experiments using Nutrient Broth and OP concentrations of (50-80 ppm) were provided in the experiments with incubation in a rotary shaker at 100 rpm for various time periods (24-90 hours). To assess the detoxification efficiency, three indicators were measured: the activity of the phosphotriesterase enzyme (a major hydrolase that catalyzes OP degradation) spectrophotometrically, bacterial viability in CFU/mL, and the percentage degradation rate of the compound. The mean detoxification efficiency was, on average, 70% maximum at the 70 ppm concentration, now, 90 hours after the detoxification assay, the particular enzyme activity, phosphotriesterases activity; was increased to 1.543 OD and the count of the amount of bacteria were 9×10⁹ CFU/mL. Optimization studies also indicated that biodegradation was very dependant on the environmental factors, and that the percentages of biodegradation were highest for pH 4 (72% degradation), or at 40°C (79% degradation), or when using peptone water as the nitrogen source (87% degradation). In general the studies provided strength in showing the ecological uniqueness, optimal environmental degradation properties of Bacillus megaterium. The metabolic substrate specificity study was unique in that it showed a high level of enzymatic activity, while Bacillus megaterium continued to grow in the presence of organophosphates (CFU -count 9×10⁹ CFU/mL), and it is here that our study suggested that this strain induced a suitable metabolic detoxification pathway, based on phosphotriesterases enzymes. The studies violent out the potential for Bacillus megaterium as a competent organism for bioremediation of pesticide-contaminated water, in as much as it is biological, post-natural and relatively inexpensive ways to remediate agricultural contamination.